Analytical Network Process (ANP) Model in Priority Scale Determination for the Bike-Sharing System Development Strategy (Jogjabike) - Noor Fatmawanti Ahmad; Dewanti Dewanti; Sigit Priyanto (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2022)
With the restrictions on the activities and travelling, many business and service sectors have been affected by the COVID-19 pandemic, one of those is transportation. This is certainly has an impact on the use of bike-sharing (JogjaBike), that is a transportation service supporting tourism. Thus, the initiation of active transport development has emerged as a response to COVID-19, therefore this research was carried out in developing a bike-sharing development strategy to support active transport in Yogyakarta. The data were collected through interviews with 9 informants with the analytical method using the Analytical Network Process (ANP). The results showed that 42% chose